Clinical development time is shorter for new anticancer drugs approved via accelerated approval in the US or via conditional approval in the EU - Ebru Demirci; Grace Omes‐Smit; Alex Zwiers (Wiley, 2023)
Abstract The US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) offer expedited regulatory approval programs for drugs with high potential patient value applicable at different stages leading to marketing authorization: (i) drug development (fast track designation (FTD), breakthrough therapy designation (BTD), regenerative medicine advanced therapy designation in the United States, and priority medicines scheme in the European Union), (ii) review of marketing authorization application (priority review in the United States and accelerated assessment in the European Union), (iii) approval of drug (accelerated approval in the United States and conditional approval in the European Union). Typical clinical development time of 76 new anticancer drugs, for which the EMA gave a positive opinion between January 2010 and December 2019, was 6.7 years: 5.8 years for small molecules and 7.7 years for biotechnology‐derived products. Drugs following only BTD (5.6 years) typically had a shorter clinical development time than drugs following only FTD (6.4 years) or both FTD and BTD (6.4 years), compared to drugs not following any expedited regulatory approval program at the drug development stage (7.7 years). Drugs following an expedited regulatory approval program at the stage of drug development and accelerated approval in the United States (FDA1 [4.5 years] and FDA3 [5.6 years]), and drugs following the standard procedure at the stage of drug development and conditional approval in the European Union (EMA5 [5.5 years] and EMA7 [4.5 years]) typically had a reduced clinical development time. These findings provide insight for the industry into combinations of expedited regulatory approval programs correlated with shorter clinical development time of new anticancer drugs.